FV 12 Longitudinal study on hippocampal volume and neuropsychological outcome in IgM-NMDAR-antibody-associated encephalopathy. Issue 10 (October 2017) - Schulze, I.; Stoppel, C.M.; Bittner, D.; Bittner, V.; von Hartrott, G.; Heinze, H.J.; Reinhold, D.; Kaufmann, J.; Körtvelyessy, P.
Abstract : Introduction: Anti-NMDAR-IgM-autoantibodies (IgM-NMDAR-aab) are occurring in approximately 4–5% of the general population (Dahm et al., 2014 ). IgM-NMDAR-aab are also associated to a rare encephalopathy presenting with symptoms resembling fronto-temporal dementia (FTD) but with much faster progression as a neurodegenerative disease (Doss et al., 2014 ). Treatment with an immunosuppressive therapy is recommend but has not been evaluated with neuroimaging and neuropsychology. Here, we present longitudinal data on two cases. Methods: We identified two patients referred to us presenting memory disturbances and memory loss together with a severe executive dysfunction and alteration in behavior developing within 3–5 months. CSF did not reveal an Alzheimer's-disease like constellation. Routine MRI scans were considered normal. Neuropsychological testing showed severe deficits in fronto-temporal functioning. Antibody screening via indirect immunofluorescence test (IFT) involved IgM-, IgA- and IgG-NMDAR-ab, Lgi-1-, CASPR2-, DPPX- and AMPA-IgG-ab and also onconeuronal ab via an immunoblot analysis (anti-Hu, -Yo, -Ri, -CV2, -Ma2, -Amphiphysin, -GAD65, -Tr(DNER), -Sox1, -Titin and -Recoverin-ab; all tests were performed by Euroimmun, Lübeck, Germany). Both patients received multiple methylprednisolone (MP) i.v. therapies (each cycle with 1 g i.v. per day for 3 days for a total of 9 g MP(Pat1) or 15 g MP(Pat2)). MRI scans were conducted during therapy and after therapy. Data were acquired on a 3-Tesla MR scanner (Siemens MAGNETOM Prisma, Erlangen, Germany) equipped with a 20-channel head coil. T1-weighted, high-resolution structural MR-images were obtained using a three dimensional MPRAGE sequence yielding an isotropic resolution of 1 mm 3 . Hippocampal volume was manually assessed via Multitracer software (free software, UCLA, USA) and double-checked. Neuropsychological assessment was identically performed for each patient during each assessment time point (Rey-Figure, Trail making test A/B, executive and memory test, digit and word-span). Results: Serum titers were highly pathological for path patients, with Pat1 having an IgM-NMDAR-aab titer of 1:160 and Pat2 of 1:320. No other abs were detected via immunoblot or IFT. In addition, results of manual assessment revealed that hippocampal (HC) volume increased bilaterally in Pat1 due to MP-treatment. Accordingly, neuropsychological measures of memory function (digit span, Rey-figure) improved slightly in Pat1. In Pat2, in contrast, only the right HC had a slight volume increase, while the left HC volume showed a slight decrease. Nevertheless, initial memory dysfunctions observed in Pat2 declined remarkably in the course of our treatment. Beyond that, clinical assessment showed an overall improvement in Pat1 and in Pat2 a complete recovery after intravenous MP-treatment. Discussion: Here, we show the first longitudinal follow-up of NMDA-aab associated encephalopathy. Treatment with MP resulted in a good to excellent improvement of clinical as well as neuropsychological assessment. These functional measures, however, were only partially mirrored by HC volume alterations during the course of the treatment. In cases of unclear dementia-like symptoms NMDAR-aab associated encephalopathy should be taken into account and treated with immunosuppressives.